Construction project management based on building information modeling (BIM) - Rui, Yin (Horizon Research Publishing, 2021)
In the construction industry, Building Information Modelling is primarily viewed as a catalyst for productivity and innovation. As projects have become more and more complex, there has been an increasing concern about the concept of project complexity. Understanding project complexity and managing contractors need to improve their management level as the rising building intricacy increases. In the construction industry, the contractors have faced many challenges, including workforce, increasing cost, inadequate risk management, unrealistic expectations/bad forecasting, limited skills, and delay problem. The project participants must coordinate and plan according to the project scope, including the construction process simulation, monitoring the construction quality, reducing rework, and improving economic benefits. Some of the main-contractor managements are trying to apply new modern technology. Building Information Modeling (BIM) is a tool used to the design, construction, and maintenance process of the whole cycle of the construction project. This article aims to analyze the BIM tool and take its advantage to improve the construction project management efficiency. The case study research approach is utilized to analyze the BIM tools. It includes the BIM 3D/4D/5D tools as the new method to build visualization model, execute clash detection, take-off quantity, simulate the construction process, make the work schedule graphically, and ensure the project is complete on time. This study is to research construction project management through applying the BIM tool. The BIM platform optimizes the design quality and improves construction work efficiencies, such as clash detection, work schedule, quantity take-off, etc. The results are also helpful for the identification of research clusters and topics in the BIM community.